2009
DOI: 10.1038/mp.2009.18
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of gene expression in two large schizophrenia cohorts identifies multiple changes associated with nerve terminal function

Abstract: Schizophrenia is a severe psychiatric disorder with a world-wide prevalence of 1%. The pathophysiology of the illness is not understood, but is thought to have a strong genetic component with some environmental influences on aetiology. To gain further insight into disease mechanism, we used microarray technology to determine the expression of over 30 000 mRNA transcripts in post-mortem tissue from a brain region associated with the pathophysiology of the disease (Brodmann area 10: anterior prefrontal cortex) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
181
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(195 citation statements)
references
References 55 publications
12
181
0
2
Order By: Relevance
“…We analysed data from seven, published, microarray‐based studies of age‐related changes in RNA expression (Barnes et al, 2011; Berchtold et al, 2008; Colantuoni et al, 2011; Kang et al, 2011; Lu et al, 2004; Maycox et al, 2009; Somel et al, 2010, 2011 ). The data came from 22 different brain regions, and the ages of the donors ranged from 20 to 106 years (Figure 1a and Supporting Information Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…We analysed data from seven, published, microarray‐based studies of age‐related changes in RNA expression (Barnes et al, 2011; Berchtold et al, 2008; Colantuoni et al, 2011; Kang et al, 2011; Lu et al, 2004; Maycox et al, 2009; Somel et al, 2010, 2011 ). The data came from 22 different brain regions, and the ages of the donors ranged from 20 to 106 years (Figure 1a and Supporting Information Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…To seek the potential genes that are differentially expressed between schizophrenia patients and healthy controls, many expression microarrays have been performed and numerous dysregulated genes have been identified. [27][28][29][30] However, we noticed that only very limited overlapping genes were identified among different expression studies, which is likely due to the use of different brain regions and quantitative methods. In addition, the quality of the analyzed samples and sample size may also influence the identification of dysregulated genes in individuals with schizophrenia.…”
Section: Introductionmentioning
confidence: 86%
“…To identify genes that are consistently dysregulated (downregulated or upregulated) in the prefrontal cortex of schizophrenia patients from different expression studies, we compared the dysregulated genes from two recent expression studies. 27,30 We found three genes (CAMKK2, CACNB3 and SNN) were consistently downregulated in both expression studies, suggesting these genes are likely high-confidence downregulated genes in schizophrenia patients compared with normal controls. In addition, we also identified two genes (WNK1 and ABCA1) that were consistently upregulated in prefrontal cortex of individuals with schizophrenia in both studies.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Levels of SNAP-25 mRNA have been reported to be increased in the superior temporal cortex of the younger group of schizophrenic patients 79 . A microarray study in the prefrontal cortex showed altered expression of genes associated with synaptic vesicle recycling in schizophrenia 80 . Accordingly, on the protein level reduced synaptophysin and SNAP-25 immunoreactivity have been detected in the prefrontal cortex 60,69,[81][82][83] .…”
Section: Schizophrenia As a Disorder Of Disturbed Synaptic Plasticitymentioning
confidence: 99%